Digital competences in Nordic teacher education - Sanne Lisborg (Oslo and Akershus University College of Applied Sciences, 2021)
We investigate how digital competences are being integrated into teacher education (TE) across the Nordic countries - Denmark, Sweden, Norway, and Finland in this article. We make the case that there has been an expansion of the agenda for digital competences in education. Digital competences have developed from an information and communication technology perspective to also include a critical, social, and creative understanding of digital technologies and computing competences. Methodologically, we make use of doc-ument analyses, qualitative questionnaires, and interviews with participants in the field. With an emphasis on Danish TE, we explore how TE in the Nordic countries has responded to this agenda on policy and institutional levels. We suggest that the Danish approach to the expanded agenda can augment tendencies and challenges in Nordic responses to digitalisation in TE. A key finding is that Nordic countries respond to the expanded agenda in different ways regarding policy regulation, content areas, and how digital com-petences are organised and distributed on a local level. Tendencies and challenges identified across Nordic countries are valuable to ensure the continual development of teachers’ digital competences.